Determinan Kinerja Perangkat Desa di Kecamatan Sekar Kabupaten Bojonegoro - Regina Wetang; Siti Sundari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The poor performance of village officials in managing village fund direct cash assistance and the allocation of village funds for village development is the basis for this research. This study aims to examine how leadership, work environment, office facilities and the competence of village officials affect the performance of village officials in Sekar District, Bojonegoro Regency. This study uses primary data. Primary data in this study were taken through questionnaires distributed directly. This research uses a quantitative approach. The population used in this study were village officials in Sekar District, Bojonegoro Regency. The number of samples used was 50 respondents and the sampling method used simple random sampling. The data analysis technique used is SEM-PLS (Partial Least Square). The results of this study indicate that leadership and office facilities affect the performance of village officials in Sekar District, Bojonegoro Regency. Meanwhile, the work environment and competence of village officials have no effect on the performance of village officials in Sekar District, Bojonegoro Regency. Keywords: Office Facilities, Leadership, Village Apparatus Performance, Village Apparatus Competence, Work Environment